language awareness in the workplace - Wshyar, Mustafa (Social Science Learning Education Journal, 2016)
Working in a team can enhance a great experience for a participant in a group work. The enhancements can be new information, the way of dealing with subject matters, and communication with people who may have different ideas. Those features are mostly very important to be existed in a person who looks for a good employment opportunity. It is a reality that most employers try to employ someone with those and some other characteristics like a good command in using technology. Integrating to a work environment is significant for an employee to perform an acceptable performance. To be a successful person in a workplace, being aware of cross cultural and different types of community of practice has its significance.